The urban sense of public space (2003)
To understand the urban space is possible after making a deep reflection on the meanings that this has had in the course of the history and who it has been developed according to the culture and the context where it is located. The article exposes clearly who it has been the evolution of the sense of the public space in the cities of the XIX and XX centuries and it proposes a reflection around its true meaning that is based on the rigorous study of the different manifestations that had had and as conclusion it outlines options that go in course with the current necessities, without leaving aside the picked up experiences, and that is an indispensable element in the construction of the architecture of the city again.